2021
DOI: 10.21203/rs.3.rs-191077/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and Genotypes in Chronic Hemodialysis Patients in Kinshasa: Prevalence and Risk Factors

Abstract: IntroductionThe steady increase in the number of chronic hemodialysis patients in sub-Saharan Africa (SSA) calls for improved management of those patients. The present study aimed to determine the frequency of hepatitis C virus (HCV) infection, the prevalent genotypes and the risk factors associated with HCV in hemodialysis patients in Kinshasa (DR Congo). MethodsA cross sectional study was conducted from February to June 2018 in all hemodialysis centers in Kinshasa. Blood samples were collected from 127 chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to HCV infection. In study by (Ngilibuma et al,2021) shows a high frequency of HCV infection in patients on chronic hemodialysis and explain that the risk factors associated with HCV infection were the number of blood transfusions, the absence of EPO treatment, the time on HD as well as the characteristics of the centers. The results of this study show 41.3% of thalassemia patients were anti HCV sera-positive .This in line with local study by (ALbakaa et al,2020) observed that male more than female with frequency 53.57 , their ages range from (2-34) years and HCV PCR positive were ( 57.14 %).…”
Section: Resultsmentioning
confidence: 98%
“…According to HCV infection. In study by (Ngilibuma et al,2021) shows a high frequency of HCV infection in patients on chronic hemodialysis and explain that the risk factors associated with HCV infection were the number of blood transfusions, the absence of EPO treatment, the time on HD as well as the characteristics of the centers. The results of this study show 41.3% of thalassemia patients were anti HCV sera-positive .This in line with local study by (ALbakaa et al,2020) observed that male more than female with frequency 53.57 , their ages range from (2-34) years and HCV PCR positive were ( 57.14 %).…”
Section: Resultsmentioning
confidence: 98%